Analisa kebocoran line warming up high pressure boiler feed pump menggunakan metode root cause and failure analysis di Pembangkit Listrik Tenaga Gas & Uap Grati - Ahmad Farhan Fuadi; Muhammad Agus Sahbana; Dadang Hermawan (TURBO [Tulisan Riset Berbasis Online], 2022)
The reliability of the Grati Gas And Steam Power Plant equipment is highly maintained to support the operational readiness of the generation. The feed water system at the Grati Gas And Steam Power Plant is one of the most important factors, especially in the feed water pump equipment. One of the pumps that is highly reliable is the High Pressure Boiler Feed Water Pump which is used as a tool for supply feed water to the Heat Recovery Steam Generator. However, from the recap data of disturbances in the Grati Gas And Steam Power Plant, leaks often occur in the system, precisely in the line warming up which serves to provide flow to the standby High Pressure Boiler Feed Water Pump and comes from the backflow of the High Pressure Feed Water Header to the Discharge side of the pump. Analysis related to the leak is very necessary in order to minimize losses due to the occurrence of the disturbance using the Root Cause And Failure Analysis method to eliminate the main disturbance causing the leak. The research variables used include the independent variable: regulating the pump discharge opening, the dependent variable: flow rate and valve warming up opening and the controlled variable: standby pump temperature and pump operating temperature. By conducting a series of trials setting the discharge valve opening of the High Pressure Boiler Feed Water Pump starting from 80%, 85%, 90%, 95% and 100%. The results of these tests can be concluded that the greater the opening of the pump discharge valve, the higher the speed and flow rate, while the pump discharge pressure will decrease.